Primary challenges for employee health and wellbeing - van Dick, Rolf (Frontiers in Organizational Psychology, 2023)
This short review listing the primary challenges for employee health and wellbeing was built utilizing three different sources: Textbook knowledge, expert opinions, and artificial intelligence. The review reveals three main topics, namely: (1) Stress and its effects on mental and physical health; (2) uncertainty coming with constant and partly dramatic organizational and societal change; and (3) work-life balance and detachment. This list of challenges may be useful for researchers designing new theories and research and for practicing managers.